Factors related to verbal bullying in elementary school students - Jamsai, Pattaraporn; Boonnak, Suteera (Kasetsart Journal of Social Sciences, 2023)
Verbal bullying in schools is a significant issue that can cause a crucial impact upon both students’ mental health and their learning. However, few studies have evidence on this issue. This research aimed to: (1) survey the ratio of students being verbal bullied in the upper elementary level; and (2) compare the ratio of students being verbal bullied in the upper elementary level according to individual factors such as gender, the time spent studying at the school, the status of the bullying, and from 12 schools which varied from demonstration schools under the Office of the Higher Education Commission (OHEC), schools under the Primary Educational Service Area Office (PESAO), and schools under Bangkok Metropolitan Administration. The total number of the target group was 1,053 students. Questionnaires were used to explore and compare the ratio of students being verbal bullied in the upper elementary schools. The factors related to being verbal bullied are the gender of the bullied, the period of time that the bullied study at the school, the status of the bullied, and from 9 schools which varied from the demonstration schools under the OHEC, the schools under the PESAO, and the schools under Bangkok Metropolitan Administration. It was found that the schools under the PESAO have a higher rate of the students being verbal bullied in the upper elementary level than the schools under Bangkok Metropolitan Administration and demonstration schools under the OHEC respectively.